Semiosis of the message in graphic design - Vilchis Esquivel, Luz de Carmen (Seven Editora, 2024)
A message is made up of one or more ideas that an individual wants to convey in some way to other individuals or a group. To emit any message, multiple verbal and non-verbal forms are used with which we access the intelligence of human beings in their capacity for understanding, reasoning and judgment. That is why we can talk about some superficial, light or trivial messages or those that are profound, complex and transcendent. The levels vary and therefore the ways in which we can communicate messages, sometimes a nudge or a glance is enough, other times we require sophisticated technology to send missives that even, due to their content, are hidden under keys, that is, they are encrypted. The essence of this phenomenon of exchange of information or knowledge is the process through which intimate, familial, socio-cultural and political ties are established. These spheres, as mentioned by Sloterdijk (Vázquez, 2006), can be the microspheres, through which coherent ontological associations between people are implanted in a physical or symbolic way, or they are abstract structures that take the form of integrated groups such as States or countries, which are the macrospheres. In the course of the actions to interrelate, associations, alliances, agreements and dependencies or dissimilarities are established, antagonisms by contrast, to mention some of the connecting nodes. The reference is to communication, this conscious dynamic that living beings develop, according to some theorists, to make something known to others. Signs play a decisive role in specifying and concretizing the emission and reception of a message, and these signs can have a diverse origin, always referring to sensory and perceptual capacities; These are collections that make up codes and these in turn constitute languages, some well identified by specialists and others in constant decoding and interpretation. DOI:https://doi.org/10.56238/sevened2024.007-019